Organisation and community intelligence in smart city leadership and beyond. Issue 1 (16th February 2022) - Gurick, Mitchell; Felger, Steven
Abstract: The relationship between smart cities and communities is anchored on the way organisations leverage technology to impact the quality of living in a city, state, or country. The emergence of smart cities has been welcomed as one of the significant breakthroughs in improving the public sector. In particular, generation of revenue, utilisation of technology, and formulation of policies are used to deal with challenges related to smart city infrastructure. Leadership is one area that has faced strategic challenges with the development of smart cities. This study aims to showcase connectivism between smart cities and communities, challenges associated with smart cities, requirements for modern leadership, and opportunities related to smart cities to improve the community.